Optimizing drug inventory application development in pharmacies through agile methodology implementation - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
This research investigates the application of Agile methods in developing drug inventory applications in pharmacies. The problems identified were the complexity of drug stock management, challenges in fulfilling drug requests and dispensing, and the risk of delay and loss of drugs that could compromise the efficiency and accuracy of inventory management. The research method involved comprehensive data collection, application development using the Agile approach, and user acceptance evaluation. The evaluation results showed a user satisfaction rate of 80%, with the application successfully meeting user needs and expectations and functioning key features such as drug stock management, ordering and procurement, and drug expiration tracking. The contribution of this research is to prove that the application of Agile methods can improve the efficiency and effectiveness of drug stock management in pharmacies and provide guidance for developing applications responsive to user needs in the healthcare industry.